ANALISIS KESEJAHTERAAN ENTREPRENEUR MUSLIM BERBASIS HOME INDUSTRI KRUPUK USEK DI KECAMATAN PANINGGARAN KABUPATEN PEKALONGAN - Mardiana, Mila (LPPM Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2022)
This study aims to explain the Analysis of Muslim Entrepreneurs' Welfare Based on the Usek Cracker Home Industry in Paninggaran District, Pekalongan Regency. This research uses a type of field research through descriptive qualitative methods. The primary data source of this research was obtained from the home industry owner of crackers which, according to our group, has the potential for research. namely Mrs. Mustaqoroh and Mrs. Niswatin. Secondary data sources were obtained from books, journals, and theses related to the research title. The results of the study concluded that the welfare of Muslim entrepreneurs based on the usek cracker home industry had been achieved and in accordance with Islamic law. This is evident starting from the production process, Entrepreneurs always apply Islamic economics in doing business. The applied Islamic economy is the embodiment of business principles, including: honesty, transparency, commitment, cooperation, discipline, care and responsibility.